Metabolomic profiles delineate mycolactone signature in Buruli ulcer disease - Niang, Fatoumata (Sci Rep, 2015)
Infection of human skin with Mycobacterium ulcerans, the causative agent of Buruli ulcer, is associated with the systemic diffusion of a bacterial macrolide named mycolactone. Patients with progressive disease show alterations in their serum proteome, likely reflecting the inhibition of secreted protein production by mycolactone at the cellular level. Here, we used semi-quantitative metabolomics to characterize metabolic perturbations in serum samples of infected individuals, and human cells exposed to mycolactone. Among the 430 metabolites profiled across 20 patients and 20 healthy endemic controls, there were significant differences in the serum levels of hexoses, steroid hormones, acylcarnitines, purine, heme, bile acids, riboflavin and lysolipids. In parallel, analysis of 292 metabolites in human T cells treated or not with mycolactone showed alterations in hexoses, lysolipids and purine catabolites. Together, these data demonstrate that M. ulcerans infection causes systemic perturbations in the serum metabolome that can be ascribed to mycolactone. Of particular importance to Buruli ulcer pathogenesis is that changes in blood sugar homeostasis in infected patients are mirrored by alterations in hexose metabolism in mycolactone-exposed cells.